A Study Of Wavelet Transforms For Data Compression And Decompression Of Audio And ECG Signals - Rosli Besar, (2004)
In this project we study the topic of wavelet transforms and how they may be used in the area of data compression and decompression of audio and electrocardiogram(ECG) signals.